Hypoxia-mediated downregulation of miRNA biogenesis promotes tumour progression - Rupaimoole, Rajesha; Wu, Sherry Y.; Pradeep, Sunila; Ivan, Cristina; Pecot, Chad V.; Gharpure, Kshipra M.; Nagaraja, Archana S.; Armaiz-Pena, Guillermo N.; McGuire, Michael; Zand, Behrouz; Dalton, Heather J.; Filant, Justyna; et al. (Nature communications, 2014)
Cancer-related deregulation of miRNA biogenesis has been suggested, but the underlying mechanisms remain elusive. Here we report a previously unrecognized effect of hypoxia in the downregulation of Drosha and Dicer in cancer cells that leads to dysregulation of miRNA biogenesis and increased tumour progression. We show that hypoxia-mediated downregulation of Drosha is dependent on ETS1/ELK1 transcription factors. Moreover, mature miRNA array and deep sequencing studies reveal altered miRNA maturation in cells under hypoxic conditions. At a functional level, this phenomenon results in increased cancer progression in vitro and in vivo , and data from patient samples are suggestive of miRNA biogenesis downregulation in hypoxic tumours. Rescue of Drosha by siRNAs targeting ETS1/ELK1 in vivo results in significant tumour regression. These findings provide a new link in the mechanistic understanding of global miRNA downregulation in the tumour microenvironment. MicroRNAs play important roles in the maintenance of cellular homeostasis through the post-transcriptional regulation of gene expression. Here, the authors implicate loss of the miRNA biogenesis factor Drosha and altered miRNA maturation in tumour progression under hypoxic conditions.